Literary Works as a Medium of Advocacy for Peace and Social Justice in Palestine: A Philosophical Value Study of Fadwa Tuqan's Poems - Liza, Fitri (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This research identify two poems by Fadwa Tuqan, "Ḥurriyyah al-Sha'b" and "Madīnatī al-Ḥazīnah", with the objective of exploring the potential of literary works as a means of advocating for sustainable peace and social justice in Palestine. An interdisciplinary approach is employed, integrating John Rawls' theory of justice, Benedict Anderson's nationalism, and Sigmund Freud's psychoanalysis, to analyse these literary texts. The data collection method involved in-depth textual analysis of the poems, focusing on the motifs of justice, nationalism, and psychological defence mechanisms revealed in the texts. The main primary source is Fadwa Tuqan's own literary work, which is used as a window to understand the collective narrative and experience of Palestinians under Israeli occupation. The main findings show that these poems are not only artistic expressions, but also manifestations of collective resilience that strengthen national identity and the spirit of resistance to oppression. The conclusion of this study is that literature, when analysed using theoretical frameworks, can play an important role in the construction of robust national narratives and the mobilisation of social solidarity in the context of political conflicts. The original contribution of this research lies in the integration of theories that are rarely connected in the context of Palestinian literature, thereby opening up new avenues for literary studies and social theory. However, it is important to note that the study is limited by the fact that it only covers two poems and that the analytical methodology could be further developed to include a wider range of literary works and alternative methodological approaches.